TINJAUAN YURIDIS TERHADAP HAK MASYARAKAT SETEMPAT KELURAHAN CILOWONG ATAS PENGELOLAAN SAMPAH TPA DI KELURAHAN CILOWONG BERDASARKAN PERATURAN DAERAH (PERDA) KOTA SERANG NOMOR 7 TAHUN 2021 TENTANG PENGELOLAAN SAMPAH DI KOTA SERANG - Ahmad Zikri Rahmatullah; Iron Fajrul Aslami; Safiulloh Safiulloh (Res Justitia : Jurnal Ilmu Hukum, 2023)
Departing from the role of the local community for decision making, implementation and supervision in the management of household waste and waste similar to household waste organized by the government, which is clearly regulated in the Serang City Regional Regulation No. 7 of 2021.This study aims to determine the rights and roles of the local community in managing waste in the Cilowong Village and how the roles and responsibilities of the government and related agencies are to implement regulations and laws in the system.Methods The research uses a descriptive method with a qualitative approach. Observations as data collection, interviews with the Head of UPT Cilowong and the Serang City Environmental Service and collecting data or news about waste management in Cilowong village.The results of the study are to show the role of the surrounding community for waste management in the area and a juridical review of the impact of the local community in the Ciliwong Village on the management of TPA waste in the Village and how the responsibilities of the Government and related agencies are in being responsible for the policies that have been generated.The conclusion from this research is that the rights of the surrounding community have not been fully fulfilled and the waste management system in the Cilowong area is not running optimally with the Serang City Regulation No. 7 of 2021 and the local government must check more about the implementation and implementation of the relevant agencies so that things are carried out in accordance with regulatory references. If the policy is implemented that is not in line with the existing regulations, the government can review the policies taken